Sistema de Coordinación y la Planificación Anual de Trabajo en la Unidad Educativa “Babahuyus - Chavez Mancheno, Katherine Del Rocío (2017)
The coordination system of the Educational Unit "Babahuyus" is developed according to the annual institutional planning, which specifies the teacher lists, student lists, academic pensum, curriculum, budgets, etc., taking into consideration the timetable granted by the Ministry of Education.